5-methylcytosine regulated CCNL2 promotes tumorigenesis and cisplatin resistance of ovarian cancer with therapeutic implications - Kai Zhang; Guiyun Cheng; Wenwen Jiang; Beihua Kong; Shu Yao; Xihan Liu (Journal of Ovarian Research)
Abstract Backgroud Ovarian cancer (OC) is the most lethal gynecological tumor, primarily due to resistance to chemotherapy. Cyclin L2 (CCNL2) is a novel member of the cyclin family and mainly localized in nucleus. It regulates transcription and alternative splicing by interacting with cyclin-dependent kinases. However, its role in OC chemoresistance remains unknown. Results Here, we demonstrated that the expression level of CCNL2 was higher in OC tissues as well as in various other tumor types. Furthermore, elevated expression of CCNL2 indicated a poor prognosis in ovarian cancer. Functionally, CCNL2 promoted OC cell proliferation and xenograft growth. Depletion of CCNL2 enhanced chemotherapy sensitivity in OC cells. Mechanistically, YBX1 directly bound to CCNL2 mRNA, and its depletion reduced CCNL2 mRNA stability and protein expression. MeRIP assays revealed that YBX1 regulated CCNL2 via 5-methylcytosine (m⁵C) modification. Mutation of the key residue of YBX1 required for m5C function led to decreased CCNL2 expression. Further investigation of the YBX1 regulatory network identified a direct interaction between YBX1 and MATR3, which cooperatively modulated downstream targets. Notably, MATR3 knockdown reversed the YBX1-induced upregulation of CCNL2. Virtual screening identified YB-B1 as a YBX1 inhibitor that effectively downregulated both YBX1 and CCNL2 expression. In vitro, YB-B1 suppressed ovarian cancer cell proliferation and enhanced cisplatin cytotoxicity. Furthermore, patient-derived tumor xenograft (PDX) model also confirmed its chemosensitizing effect. Conclusions In summary, we demonstrated that CCNL2 promoted OC cell proliferation and chemoresistance, with its expression regulated by YBX1 via m5C methylation. The small molecule inhibitor YB-B1 was identified as a promising solution to overcome chemotherapy resistance. Clinical trial number Not applicable.